Racial ethnic differences in type 2 diabetes treatment patterns and glycaemic control in the Boston Area Community Health Survey. Issue 5 (12th May 2015) - Goonesekera, Sunali D; Yang, May H; Hall, Susan A; Fang, Shona C; Piccolo, Rebecca S; McKinlay, John B
Abstract : Objectives: Numerous studies continue to report poorer glycaemic control, and a higher incidence of diabetes-related complications among African–Americans and Hispanic–Americans as compared with non-Hispanic Caucasians with type 2 diabetes. We examined racial/ethnic differences in receipt of hypoglycaemic medications and glycaemic control in a highly insured Massachusetts community sample of individuals with type 2 diabetes. Setting: Community-based sample from Boston, Massachusetts, USA. Participants: 682 patients with physician-diagnosed diabetes from the third wave of the Boston Area Community Health Survey (2010–2012). The study included approximately equal proportions of African–Americans, Hispanics and Caucasians. Methods: We examined racial/ethnic disparities in diabetes treatment by comparing proportions of individuals on mutually exclusive diabetes treatment regimens across racial/ethnic subgroups. Using multivariable linear and logistic regression, we also examined associations between race/ethnicity and glycaemic control in the overall population, and within treatment regimens, adjusting for age, gender, income, education, health insurance, health literacy, disease duration, diet and physical activity. Results: Among those treated (82%), the most commonly prescribed antidiabetic regimens were biguanides only (31%), insulin only (23%), and biguanides and insulin (16%). No overall racial/ethnic differences in treatment or glycaemic control (per cent difference for African–Americans: 6.18, 95% CI −1.00 to 13.88; for Hispanic–Americans: 1.01, 95% CI −10.42 to 12.75) were observed. Within regimens, we did not observe poorer glycaemic control for African–Americans prescribed biguanides only, insulin only or biguanides combined with insulin/sulfonylureas. However, African–Americans prescribed miscellaneous regimens had higher risk of poorer glycaemic control (per cent difference=23.37, 95% CI 7.25 to 43.33). There were no associations between glycaemic levels and Hispanic ethnicity overall, or within treatment regimens. Conclusions: Findings suggest a lack of racial/ethnic disparities in diabetes treatment patterns and glycaemic control in this highly insured Massachusetts study population. Future studies are needed to understand impacts of increasing insurance coverage on racial/ethnic disparities in treatment patterns and related outcomes.